Development of News Text Writing E-Module Designing The Concept of Differentiation for Senior High School Students - Aegustinawati Aegustinawati; Yeti Mulyati; Khaerudin Kurniawan (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This research aims to produce a product as an e-module for writing news texts with the concept of differentiation. The research method used was Research and Development (R&D) with the ADDIE model consisting of five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through observation, interviews, questionnaires, and initial tests of news text writing ability. The data sources were teachers and students of grade XI grade XI high school. Based on the needs analysis data, the e-module was designed and developed, then validated by material experts, learning experts, media experts, and expert practitioners. The data analysis technique used quantitative and qualitative analysis. Expert validation showed that this product was